Cytochrome P450 monooxygenase-mediated eicosanoid pathway: A potential mechanistic linkage between dietary fatty acid consumption and colon cancer risk - Weicang Wang; Jianan Zhang; Guodong Zhang (Food Science and Human Wellness)
Human consumption of linoleic acid (LA, 18:2ω-6, abundant in vegetable oils) is very high. Animal experiments showed that excessive LA intake increased azoxymethane-induced colon tumorigenesis, however, the impact of excessive LA on colon cancer in human is not conclusive, making it difficult to make dietary recommendations for optimal intake of LA. Understanding the molecular mechanisms of LA on colon tumorigenesis could help to clarify its health effect, and facilitate development of mechanism-based strategies for preventing colon cancer. Recent studies show that the previously unappreciated cytochrome P450 monooxygenase-mediated eicosanoid pathway is upregulated in colon cancer and plays critical roles in its pathogenesis, and could contribute to the effects of dietary LA, as well as ω-3 fatty acids, on colon tumorigenesis. In this review, we will discuss recent studies about the roles of cytochrome P450 monooxygenases in fatty acid metabolism and its roles in colonic inflammation and colon cancer, and how this information could help us to clarify the health impacts of dietary fatty acids. Keywords: Linoleic acid, Polyunsaturated fatty acids, ω-3 Fatty acids, Colon cancer, Colonic inflammation, Cytochrome P450, Eicosanoids